PENGARUH KEJADIAN FLEBITIS DENGAN PELAKSANAAN PEMASANGAN INFUS SESUAI DENGAN SOP DI RUANG PERAWATAN PENYAKIT DALAM TAHUN 2022 - Kazael Octaviani; Febi Ratnasari; Ayu Pratiwi (Nusantara Hasana Journal, 2023)
Phlebitis is an inflammation of the vein caused by chemical or mechanical irritation characterized by redness, pain, swelling, heat, and hardness at the puncture site or along the vein. Based on a preliminary study from the Nosocomial Infection Control surveillance team at the Pakuhaji Hospital, Tangerang Regency, it can be seen that the incidence of phlebitis in December 2021 was 3.7 per mil. The incidence of phlebitis in January to December 2021 was 176 cases. The purpose of this study was to determine the effect of phlebitis incidence with the implementation of infusion in accordance with the SOP in the Internal Medicine Room in 2022. Research design The design of this study was Pre experimental with One Group Pretest-Posttest Design. Research results: Wilcoxon Sign Test results show that the Z value for the variable incidence of phlebitis and infusion is -0.3.78b with p value Asymp. Sig. (2-tailde) of 0.705 (> 0.05), it can be concluded that "Ha/HI is rejected" meaning that there is no difference between the implementation of infusion and the incidence of phlebitis. Conclusion: there is no effect between the implementation of infusion in accordance with the SOP and the incidence of phlebitis in the Internal Medicine Room.